Pengelolaan Arsip Dinamis Berbasis Elektronik di Kantor Kecamatan Cileunyi dalam Mempermudah Kegiatan Temu Kembali Arsip - Anjani, Sri; Sukaesih, Sukaesih; Prahatmaja, Nurmaya (Prodi Ilmu Perpustakaan dan Informasi Universitas Islam Negeri Raden Fatah Palembang, 2023)
Archives have an important role in supporting the smooth running of the main tasks and functions of an institution, including sub-district level government agencies such as Cileunyi District. Along with technological developments, the archives being managed are now not only in printed form but also available in electronic form. the existence of electronic archives certainly requires a management that is different from the management of printed archives. Through the use of technology, archive management at the Cileunyi District Office in the process becomes more effective and efficient. The purpose of this study was to determine the management of electronic dynamic archives at the Cileunyi District Office in facilitating archive retrieval activities that focus on several processes such as creation and storage, distribution and use, maintenance and disposition. This study uses a qualitative method. The results showed that electronic-based dynamic archive management at the Cileunyi District Office had been carried out by adjusting to existing capabilities and resources, but various deficiencies were found which became obstacles that could hinder the electronic archive management process including: (a) lack of human resources as archive manager, (b) there is no filing department, (c) there is no scanner machine and electronic record management system, and (d) no depreciation activities are carried out which have an impact on increasingly limited storage space.